2012
DOI: 10.1155/2012/615835
|View full text |Cite
|
Sign up to set email alerts
|

Links between Metabolic Syndrome and Cardiovascular Autonomic Dysfunction

Abstract: Background. Type 2 diabetes (T2D) might occur within metabolic syndrome (MbS). One of the complications of T2D is an impaired (imp) cardiovascular autonomic function (CAF). Aims. In subjects with T2D and age ≤ 55 years, the prevalence of impCAF and its relationship with BMI, waist, HbA1c values, MbS, hypertension, and family history of T2D and/or hypertension were analysed. Methods. 180 subjects consecutively undergoing a day hospital for T2D were studied. The IDF criteria were used to diagnose MbS. To detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
1
27
1
Order By: Relevance
“…Overweight also has a negative effect on glycaemic control. In this line of evidence in our study we demonstrate a significant association between high HbA1c values (HbA1c >7.0%) and the occurrence of at least one abnormal test [8]. HbA1c is an established parameter to assess mean glycemia over the preceding 3 months.…”
Section: Impaired Autonomic Function In Metabolic Syndrome and Diabetessupporting
confidence: 77%
See 3 more Smart Citations
“…Overweight also has a negative effect on glycaemic control. In this line of evidence in our study we demonstrate a significant association between high HbA1c values (HbA1c >7.0%) and the occurrence of at least one abnormal test [8]. HbA1c is an established parameter to assess mean glycemia over the preceding 3 months.…”
Section: Impaired Autonomic Function In Metabolic Syndrome and Diabetessupporting
confidence: 77%
“…Both PH and decreased heart rate variability are more frequent and severe 5 years after the diagnosis of Diabetes [36]. Unexpectedly, we found no association between CAF score and the duration of Diabetes, however, the subjects of our cohort [8], probably had a better metabolic memory than that of subjects from previous studies, not only because they were younger than those considered in previous studies, but also because they experienced a program of education to healthy life-style together with insulin and /or oral antidiabetic agents of last generation since the onset of Diabetes.…”
Section: Impaired Autonomic Function In Metabolic Syndrome and Diabetescontrasting
confidence: 58%
See 2 more Smart Citations
“…Recent studies have indicated that CAN is associated with many other majority segments of the general population, such as the elderly and patients with HTN and metabolic disorders [5,7,8]. Studies have provided evidence that CAN is common in persons with an impaired glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%